KESENIAN TRADISIONAL ANGKLUNG DALAM PERSPEKTIF FILSAFAT ILMU: KAJIAN EPISTEMOLOGI, ONTOLOGI, & AKSIOLOGI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Angklung is one of Indonesia's traditional cultural heritages that functions not only as a musical instrument but also as a symbol of cultural identity, a means of social expression, and a medium for passing down the values of the Sundanese community. This study aims to analyze angklung from the perspective of the philosophy of science, focusing on three main branches, namely ontology, epistemology, and axiology, to gain a deeper understanding of its essence, the process of knowledge, and the values contained within it. This research uses a qualitative method with a library research approach. Data were obtained from various written sources such as scholarly books, journal articles, research reports, theses, and other relevant documents. Data analysis was conducted through the stages of reading, noting, and grouping data according to the focus of the study, while data validity was tested through source triangulation. The results of the study indicate that ontologically, the angklung is a multidimensional cultural entity, encompassing both material and non-material dimensions related to historical, social, spiritual, and ritual aspects. Epistemologically, knowledge about the angklung is built through traditional oral and practical inheritance, and it is further systematized through formal education and modern cultural institutions. Meanwhile, axiology shows that the angklung contains aesthetic values, a sense of togetherness, character education, cultural identity, and social ideology oriented towards human welfare. Thus, the angklung is not only artistically valuable but also holds philosophical and educational significance in contemporary society.